A circular economy approach to building heating: The role of exergy in policymaking. (October 2021) - North, Peter; Jentsch, Andrej
Abstract: Building heating accounts for 17% of the United Kingdom's (UK) direct greenhouse gas (GHG) emissions and is the third largest emitter after surface transport and industry. There is a significant potential for building CO2 emission reductions to contribute towards the UK's 2050 net zero-carbon target. The UK Government's approach to decarbonising building heating centres on reducing the energy demand of buildings and displacing the use of fossil fuels with low to zero-carbon and renewable energy technologies. While this approach can minimise energy consumption, it continues to quickly downcycle resources through a linear economy approach of take–make–waste. There is no consideration of how effective the technologies are in their efficient use of the primary energy resources (PER), with some technologies being far more wasteful in terms of energy resource consumption than others. This strategy will lead to an increasing, and avoidable burden on the national electricity infrastructure as heat becomes increasingly electrified towards 2050 and that will translate to higher costs for both consumers and the economy. A similar outcome would result from the use of renewable electricity to produce hydrogen for building heating. Larger cities have more local heat sources available in the form of waste heat and environmental heat (in the ground and water) than there is building heat demand. A circular economy approach requiring new regulation and policy can prioritise the reuse of these freely available heat sources enabled by heat networks to realise a more sustainable approach to building heating. This will ultimately result in the decoupling of resource consumption from its depletion, which is a key circular economy principle. Exergy analysis used in city energy planning can identify and prioritise those more resource-efficient system options that utilise local heat sources and better conserve primary energy resources. The implementation of more resource-efficient heat supply systems can reduce energy resource consumption by over two-thirds and avoid the need to reinforce the national electrical infrastructure thus keeping citizens' heating costs down.